2017
DOI: 10.22146/jae.24208
|View full text |Cite
|
Sign up to set email alerts
|

Financial Feasibility of Sijuk Shrimp Paste Business in Sungai Padang Village, Sijuk District, Belitung Regency

Abstract: Sijuk shrimp paste business is a business in processing rebon shrimp which is most commonly implemented in Belitung Regency. Therefore, financial feasibility needs to be done by considering the fluctuation in the number of catches of rebon shrimp in nature that will affect the Sijuk shrimp paste business financially. In this study, profit analysis, investment feasibility, and sensitivity were used to draw the conclusions. The samples involve 25 shrimp paste businesses taken by using census method in Sungai Pad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…This can be achieved by either simulation using different mathematical models or by conducting actual trials [372]. To significantly save time and cost for process development, simulation has been used to analyse technical and economic feasibility of industrial production of proteins from different SPBs (kingfish [373], catfish [374], tuna [375], and shrimp [376]) and microalgae [377,378]). Industrial production of fish protein hydrolysate (FPH) from yellow tail kingfish processing by-products (YTKPBs) by chemical and enzymatic hydrolysis with microwave intensification was simulated using a commercial simulator, SuperPro Designer [373].…”
Section: Economic Feasibility and Industrial Production Of Protein-bamentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved by either simulation using different mathematical models or by conducting actual trials [372]. To significantly save time and cost for process development, simulation has been used to analyse technical and economic feasibility of industrial production of proteins from different SPBs (kingfish [373], catfish [374], tuna [375], and shrimp [376]) and microalgae [377,378]). Industrial production of fish protein hydrolysate (FPH) from yellow tail kingfish processing by-products (YTKPBs) by chemical and enzymatic hydrolysis with microwave intensification was simulated using a commercial simulator, SuperPro Designer [373].…”
Section: Economic Feasibility and Industrial Production Of Protein-bamentioning
confidence: 99%
“…Based on modelled feasibility, one industrial plant (SAMPI) with a designed capacity of 3000 tonnes/year was built in Port Lincoln, South Australia to produce commercial fish protein hydrolysate from tuna and kingfish processing by-products using enzymatic hydrolysis [ 379 ]. Similarly, industrial production of fish protein concentrate and crude enzymes was also shown to be economically feasible at industrial scale for catfish processing by-products [ 374 ], gelatine from tuna [ 375 ], shrimp paste [ 376 ], and microalgal proteins [ 378 ]. Enzymatic hydrolysis for production of collagen hydrolysate from codfish skin was successfully scaled up from a laboratory scale to pilot and plant scales with capacity of 100 and 2000 L, respectively [ 380 ].…”
Section: Process Development For Production Of Proteins and Proteimentioning
confidence: 99%
“…Gross Benefit-Cost Ratio (Gross B/C Ratio) merupakan perbandingan antara Present Value Benefit dengan Present Value Cost (Nugraha et al, 2017). Kriteria penilaian Gross B/C Ratio sebagai berikut: Gross B/C > 1 : proyek UD.…”
Section: Metode Penelitianunclassified
“…Determination of financial aspects that are worth using to provide an overview of business capability that has been running then can be evaluated to assist in making decisions for the future [7]. Financial feasibility is divided into several aspects, such as the use of input, financial reports, profit, and feasibility analysis, and the last part is the determinant analysis result of whether the business is feasible to continue or not based on the three previous aspects [8]. However, the current challenges many entrepreneurs face are management weaknesses and the absence of financial records, which impact entrepreneurs' ignorance of financial performance and lead to difficulties in obtaining capital [9].…”
Section: Introductionmentioning
confidence: 99%